ANALISIS DAN RESPON RISIKO PADA PROYEK KONSTRUKSI GEDUNG - Yayah Sopiyah; A’isyah Salimah (Politeknik Negeri Jakarta, 2020)
High-rise Building construction projects can be said as high-risk projects, this is based on the construction process which usually takes a long time and is complex, so that it can cause uncertainties that create various risks. Risk is a combination of the probability of an event and the impact of that event. The impact of risks can affect productivity, quality and project cost budgets. The purpose of this study is to identify the risks that occur in the magnitude of the influence on building construction projects and analyze the risk responses that occur at building construction projects. In this research, risk analysis, risk identification and risk response carried out at two different building construction projects with two different contractors. Risk identification carried out by conducting a literature study, assessing the frequency / probability of risk and assessing the impact of risks using the Severity Index, identifying risks using the Probability Impact Matrix. From the results of the analysis it has been concluded that there is one risk variable that is included in the large category, the risk variable is the